Community Perspectives on Air Pollution and its Related Health Risks: A Case Study of Tehran (2012-2013) - Mahsa Jahangiri-Rad (علوم بهداشتی ایران, 2014)
Abstract Background and purpose:Recent perspectives on public understandings of global environmental risk have emphasized the interpretation, judgment and sense-making “that takes place, modes of perception that are inextricably tied to aspects of and local” context. The main interest of this study is to observe the socio-demographic (gender, age, and education) differences in awareness of pollution and sources of air pollution. Materials and Methods:The target population of this study were adult (>25 years) inhabitants of Tehran city. The information is gathered through a questionnaire conducted in various study areas then compared with demographic variables. Results:Awareness of air pollution was highly found in higher educated of men, while this same result was observed within the women with lower education (under diploma). The results also showed that women in both groups are more concerned with all of the pollution than men. Conclusion:With regard to health impacts, men perceived air pollution to be associated with respiratory disease, whereas women perceive asthma to be associated with air pollution.